Implementation of the Independent Curriculum in Technology-Based Islamic Education Learning Responds to Changes in Students' Attitudes - Faizuddin, Faizuddin; Wasehudin, Wasehudin (The Magister of Islamic Education IAIN Pontianak, 2024)
The important role of Islamic Religious Education (PAI) learning in shaping character, morals, and strengthening spiritual and religious values in students in the Industry 4.0 era. This study aims to examine the implementation of the independent curriculum in PAI learning with a focus on technology integration as a response to changes in community attitudes and the demands of the increasingly developing world of work. The research method used is a qualitative approach with literature analysis and in-depth interviews with PAI teachers. The results of the study show that the integration of technology in PAI learning not only improves the quality of learning, but also facilitates the development of relevant attitudes and skills, such as creativity, collaboration, and adaptation. As a result, PAI education that is integrated with technology and strengthens spiritual values is the key to preparing students to face challenges and opportunities in the Industry 4.0 era, as well as forming a generation that is ready to face rapid global change